2021
DOI: 10.1155/2021/6671870
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Asthma among Iranian Children and Adolescent: A Systematic Review and Meta‐Analysis

Abstract: Background. Asthma is an important reason for hospitalization in children aged under five years. Information about the current status of asthma in Iranian children can help the Iranian health sector plan carefully and prevent asthma incidence by educating the families. The present systematic review and meta-analysis is aimed at estimating asthma prevalence in Iranian children and adolescents. Method. Data were found using keywords such as prevalence, epidemiology, asthma, adolescent, children, pediatrics, Iran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
(36 reference statements)
0
9
0
1
Order By: Relevance
“…The prevalence of asthma in children was 6%; in adolescents, it was 8%. The prevalence was 8%-9% in girls and boys, respectively [ 35 ]. In Golestan Province, northern Iran, in 2014, Mehrvar et al reported the overall prevalence of current asthma and asthma ever symptoms as 9.5% and 7.5%, respectively, with a higher prevalence of asthma in the age group of 13–14 years than in the age group of 6–7.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of asthma in children was 6%; in adolescents, it was 8%. The prevalence was 8%-9% in girls and boys, respectively [ 35 ]. In Golestan Province, northern Iran, in 2014, Mehrvar et al reported the overall prevalence of current asthma and asthma ever symptoms as 9.5% and 7.5%, respectively, with a higher prevalence of asthma in the age group of 13–14 years than in the age group of 6–7.…”
Section: Discussionmentioning
confidence: 99%
“…As to the sex-related difference, we found that the positive rate of allergens and the percentages of double-allergen sensitizations in boys were substantially higher in the total population, and the sensitizations of Der.f, Der.p , and ragweed in boys were higher than those in girls. The reason for sex differentiation may be related to hormone levels ( 18 , 19 ). However, further studies should be conducted to unveil the precise mechanisms related to the differences in age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…6 The documented prevalence of asthma among Iranian children and adolescents has been 6% and 8%, respectively. 7 According to a recent survey conducted in Karaj, 10.52% of 13-14-year-old adolescents, had experienced wheezing in the past 12 months. 8 The International Study of Asthma and Allergy in Childhood (ISAAC), started in 1991, aimed to assess the prevalence of asthma and allergic diseases in various countries.…”
Section: As the Most Prevalent Chronic Inflammatory Diseasementioning
confidence: 99%